The gender implications of large-scale land deals - Behrman, Julia A.; Meinzen-Dick, Ruth S.; Quisumbing, Agnes R. (International Food Policy Research Institute, 2011)
Whether viewed as “land grabs” or as agricultural investment for development, large-scale land deals by investors in developing countries are generating considerable attention. However, investors, policymakers, officials, and other key stakeholders have paid little attention to a dimension of these deals essential to truly understanding their impact: gender. It is easy to laud outside investment in agriculture, or to deride land deals and the accompanying processes as bad or unfair, without looking at the benefits and costs to local men and women. The results of land deals depend in part on the prior rights and responsibilities of women and men and in part on how the land deal's implementation perpetuates, improves, or distorts these rights and responsibilities. A wide-ranging body of evidence forms a clear rationale for prioritizing gender issues in agriculture. Households often do not act as a single unit when allocating food and nonfood resources, which means all household members may not benefit from providing the male household head with more income. Evidence shows that improvements in household agricultural productivity, food security, and nutrition must address women's needs because, in many parts of the world, women are more likely than men to spend the income they control on food, healthcare, and their children's education. Conversely, land deals can reduce the welfare of women and their families, even if men's income increases. Land-related investments promoted in the name of “rural development” will miss their mark unless the many actors involved—including national and local governments, nongovernmental organizations (NGOs), the research community, and investors—recognize and address the needs of women as well as men.